Trace metal contamination in surface sediments of intertidal zone from Qinhuangdao, China, revealed by geochemical and magnetic approaches: Distribution, sources, and health risk assessment. Issue 1 (15th April 2016) - Zhu, Zongmin; Xue, Junhui; Deng, Yuzhen; Chen, Lin; Liu, Jiangfeng
Abstract: Based on geochemical and magnetic approaches, the distribution, sources, and health risk of trace metals in surface sediments from a seashore tourist city were investigated. A significant correlation was found between magnetic susceptibility (χ) and trace metals, which suggested that levels of trace metals in the sediments can be effectively depicted by the magnetic approach. The spatial distribution of χ and trace metals matched well with the city layout with relatively higher values being found in the port and busy tourist areas. This result, together with enrichment factors (EFs) and Tomlinson pollution load index (PLI) of metals, suggested that the influence of human activities on the coastal environment was noticeable. Principal component analysis (PCA) indicated that trace metals in the sediments were derived from both anthropogenic and natural sources. Noncarcinogenic risk assessment showed that there was no potential health risk of exposure to metals by means of ingestion or inhalation. Highlights: Trace metals in sediments were determined by geochemical and magnetic approaches. There was significant correlation between trace metals and magnetic susceptibility. The enrichment of trace metals in sediments was noticeable. Health risk of trace metals in sediments for children was not serious.